Barrier in Design Innovation of Fashion Business: Evidence from Indonesian Moslem Fashion SME - Sari, Rora P.; Asad, Nabila (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2018)
This paper aims to explore barriers that prevent Moslem fashion industry to adopt and indulge more innovative apparel and accesories design. As Moslem fashion gains more popularity in Indonesia, Moslem fashion is now adapting a more modern and contemporary approach rather than using the traditional method in designing the apparel and accessories product lines for the customers. Nevertheless, Moslem fashion industry also faced barriers in pursuing and creating an innovative product design in order to gain the competitive advantage in the industry. There were 70 personal communications conducted from SME Moslem fashion key personnels across Indonesia. This research applied qualitative approach, mostly using semi-structured interview’s techniques in exploring the barriers of innovation from each SMEs. As the result, it was found that human resource barrier (lack of skills and shortage of skilled staffs), operational resource barrier (rare raw materials and difficculties to find a high-quality material), financial problem (high cost in innovation, lack of fund and poor financial management) and imitations from competitors were the most prominent factors that prevent Moslem fashion SME brands to create innovative apparel design and innovative fashion product lines.